Gebed in die liturgie: 'n prakties-teologiese verkenning - Cas Wepener (Acta Theologica)
For many worshippers, prayer in the worship service is not always appropriated positively. In this article, a practical theological exploration regarding prayer in the liturgy is undertaken. By means of a spiral movement between theory and praxis, the phenomenon is scrutinised. After a description of the current practice and an attempt at explaining this state of affairs, the work of three liturgists is presented for a more normative perspective. Finally, some guidelines are formulated for a renewed theory for praxis in the light of the preceding exploration. In essence, it is argued that prayer is an essential part of the Reformed liturgy for which good preparation is essential and that a re-appreciation of the rightful place and meaning of (different forms of) prayer in the liturgy can contribute to enrich the practice for both worshippers and those leading in worship.